Efficacy and safety of prolonged 3-year telbivudine treatment in patients with chronic hepatitis B - Gane E. (2017)
Background: In the GLOBE trial, telbivudine demonstrated superior efficacy to lamivudine at 2 years in patients with chronic hepatitis B (CHB). Aims: To investigate the long-term efficacy and safety of telbivudine in the telbivudine-treated cohort from the GLOBE trial. Methods: Virological and biochemical responses were assessed in 213 HBeAg-positive and 186 HBeAg-negative CHB patients who continued telbivudine treatment for 3 years. Results: Undetectable hepatitis B virus DNA and HBeAg seroconversions were achieved by 77 and 37% of HBeAg-positive patients respectively. Cumulative HBeAg seroconversion rate was 46%. HBeAg seroconversion was sustained at 52 weeks off therapy in 84% of the patients enrolled in the off-treatment follow-up arm of the study. Undetectable viraemia and normal alanine aminotransferase (ALT) levels at 3 years were achieved by 85 and 83% of HBeAg-negative patients respectively. Genotypic resistance rates for the study population who continued therapy during the third year were 11.3 in HBeAg-positive and 6.5% in HBeAg-negative patients. Patients with undetectable viraemia at treatment week 24 had optimal outcomes at 3 years. In the HBeAg-positive population, cumulative HBeAg seroconversion occurred in 58%. Resistance rates for HBeAg-positive and HBeAg-negative patients were 3.6 and 6.2% respectively. The telbivudine safety profile during prolonged therapy was similar to that in the GLOBE trial. Conclusions: Three years of telbivudine treatment yielded high rates of viral suppression and ALT normalization with a favourable safety profile. High rates of HBeAg seroconversion were achieved with prolonged telbivudine therapy and were sustained in the majority of patients over 52 weeks off therapy. © 2011 John Wiley Sons A/S.